Flexible composite phase change material with enhanced thermophysical, dielectric, and mechanical properties for battery thermal management. (1st August 2022) - Cao, Jiahao; Ling, Ziye; Lin, Xuemin; Wu, Yi; Fang, Xiaoming; Zhang, Zhengguo
Abstract: A flexible composite phase change material (FCPCM) reduces thermal contact resistance in battery thermal management systems (BTMSs), thereby improving heat transfer efficiency. However, its high electrical and low thermal conductivity hinders its application to cooling lithium-ion batteries. Herein, a type of FCPCM with well-retained flexibility as well as high electrical insulation and thermal conductivity is prepared by mixing paraffin (PA), styrene ethylene butylene styrene (SEBS), and hexagonal boron nitride (h-BN). The chemical, thermophysical, and mechanical properties, as well as the physical structure of the FCPCM are analyzed. The components (PA/SEBS/BN) show good physicochemical compatibility without chemically reacting. The shore hardness of the proposed FCPCM decreases from 80 to 9 HA as the temperature increases from 20 to 80 °C, and it can be easily stretched or bended beyond the melting point of PA. Moreover, this composite possesses large latent heat (127.8 J/g), high thermal conductivity (2.7 W/(m·K)), sufficient volume resistivity (20, 106 Ω·m), and suitable phase change temperature (41.1 °C). With such exceptional qualities, it shows outstanding applicability and cooling performance in cylindrical and prismatic batteries. Temperature and temperature difference of the prismatic battery pack can be restrained below 45 °C and 4 °C, even at a high discharge rate of 6 C and an ambient temperature of 38 °C. Graphical abstract: Unlabelled Image Highlights: A novel flexible composite phase change material (FCPCM) is synthesized. FCPCM shows a high flexibility when the temperature is above the melting point. FCPCM possesses high thermal conductivity, dielectric, and mechanical properties. FCPCM cooling pad is effective for cooling Lithium-ion batteries.